ANALYSIS OF THE SYSTEMS OF TEXT PLAGIARISM DETECTION - Заболотна, Ірина; Махньова, Аліна; Комлев, Андрій; Заболотный, Александр (SWorldJournal, 2024)
Plagiarism becomes more common every year. Availability of information is the basis for it. Textual plagiarism is full or partial borrowing of text fragments. To detect it there are used information technologies and specialized software that are constant